Compositions and Abundances of Sulfate-Reducing and Sulfur-Oxidizing Microorganisms in Water-Flooded Petroleum Reservoirs with Different Temperatures in China - Tian, Huimei; Gao, Peike; Chen, Zhaohui; Li, Yanshu; Li, Yan; Wang, Yansen; Zhou, Jiefang; Li, Guoqiang; Ma, Ting (Frontiers in Microbiology, 2017)
Sulfate-reducing bacteria (SRB) have been studied extensively in the petroleum industry due to their role in corrosion, but very little is known about sulfur-oxidizing bacteria (SOB), which drive the oxidization of sulfur-compounds produced by the activity of SRB in petroleum reservoirs. Here, we surveyed the community structure, diversity and abundance of SRB and SOB simultaneously based on 16S rRNA, dsrB and soxB gene sequencing, and quantitative PCR analyses, respectively in petroleum reservoirs with different physicochemical properties. Similar to SRB, SOB were found widely inhabiting the analyzed reservoirs with high diversity and different structures. The dominant SRB belonged to the classes Deltaproteobacteria and Clostridia, and included the Desulfotignum, Desulfotomaculum, Desulfovibrio, Desulfobulbus and Desulfomicrobium genera. The most frequently detected potential SOB were Sulfurimonas, Thiobacillus, Thioclava, Thiohalomonas and Dechloromonas, and belonged to Betaproteobacteria, Alphaproteobacteria, and Epsilonproteobacteria. Among them, Desulfovibrio, Desulfomicrobium, Thioclava, and Sulfurimonas were highly abundant in the low-temperature reservoirs, while Desulfotomaculum, Desulfotignum, Thiobacillus, and Dechloromonas were more often present in high-temperature reservoirs. The relative abundances of SRB and SOB varied and were present at higher proportions in the relatively high-temperature reservoirs. Canonical correspondence analysis also revealed that the SRB and SOB communities in reservoirs displayed high niche specificity and were closely related to reservoir temperature, pH of the formation brine, and sulfate concentration. In conclusion, this study extends our knowledge about the distribution of SRB and SOB communities in petroleum reservoirs.